Correlation of COL1A2 gene polymorphisms with dental fluorosis in mexican children - Muñoz Hernández, Manuel de Jesús; Burciaga Nava, Jorge Alberto; Cuevas Gonzalez, Juan Carlos; Zambrano Galván, Graciela (Acta Universitaria, 2017)
Dental fluorosis (FD, for its achronym in spanish) is the hypomineralization of dental enamel caused by increased porosity, severity is due to an excessive intake of fluoride with a dose-response relationship during enamel development. The objective of this study was to determine correlation of rs810687 and rs411717 polymorphisms of (colageno tipo 1 alfa 2) COL1A2 gene with FD in Mexican children aged 10 to 12 years, using Dean Index to establish degree of FD and PCR-HRM for polymorphisms genotyping. We included 100 children of 10.9 ± 0.78 years; Allele and genotype frequencies found were: G = 52.5%, A = 47.5%, G/G = 27.5%, G/A = 49.8%, A/A = 22.5%, C = 63.3%, T = 36.5%, C/C = 40.3%, C/T = 46.3%, T/T = 13.3% of rs810687 and rs411717 polymorphisms respectively; with a Pearson correlation coefficient r =–0.017 (p > 0.05) with FD. Results showed that there was no correlation between FD and presence of rs810687 and rs411717 polymorphisms of the COL1A2 gene.
Keywords: Array; Array; Array; Array